Classroom Environments That Promote Learning from the Perspective of School Children - Castro Pérez, Marianella (2015)
The following paper is based on a research41 made on school environments that promote learning in children. Its objective was “to determine the physical and socio-emotional factors of school environments that promote learning.” To this end, the investigation had both an exploratory and descriptive approach in terms of the various physical and emotional elements that influence the classroom environment and, therefore, the learning process. In this paper, reference is made only to the data provided by the child population. Such group was comprised of 307 boys and girls of public schools from six provinces in the country, intentionally selected through coordination and negotiation with the authorities of schools that agreed to participate. The data collection instruments used were two questionnaires with closed and open questions, an anecdotal record, and a guide on which the observation technique was performed. The analysis of the information derived from the technique and instruments used was developed by complementing quantitative data with qualitative data. Emerging categories were created to interpret the latter. The information provided by the boys and girls will hopefully serve as input to raise awareness among universities, authorities and teachers about the imperative need for school environments that are aesthetic, pleasant, motivating, comfortable, clean and promote the emotional stability every human being requires for the learning process to be successful.